Impact of oxidative posttranslational modifications of SERCA2 on heart failure exacerbation in young patients with non-ischemic cardiomyopathy: A pilot study - Takumi Toya; Kei Ito; Kazuki Kagami; Ayumu Osaki; Atsushi Sato; Toyokazu Kimura; Shunpei Horii; Risako Yasuda; Takayuki Namba; Yasuo Ido; Yuji Nagatomo; Katsumi Hayashi; et al. (International Journal of Cardiology: Heart & Vasculature, 2020)
Background: Oxidative posttranslational modifications (OPTM) impair the function of Sarcoplasmic/endoplasmic reticulum (SR) calcium (Ca2+) ATPase (SERCA) 2 and trigger cytosolic Ca2+ dysregulation. We investigated the extent of OPTM of SERCA2 in patients with non-ischemic cardiomyopathy (NICM). Methods and results: Endomyocardial biopsy (EMB) was obtained in 40 consecutive patients with NICM. Total expression and OPTM of SERCA2, including sulfonylation at cysteine-674 (S-SERCA2) and nitration at tyrosine-294/295 (N-SERCA2), were examined by immunohistochemical analysis. S-SERCA2 increased in the presence of late gadolinium enhancement on cardiac magnetic resonance imaging. S-SERCA2/SERCA2 and N-SERCA2/SERCA2 correlated with cardiac fibrosis evaluated by Masson’s trichrome staining of EMB. SERCA2 expression modestly increased in parallel with an upward trend in OPTM of SERCA2 with aging. This tendency became prominent only in patients aged >65 years. OPTM of SERCA2 positively correlated with brain natriuretic peptide (BNP) values only in patients aged ≤65 years. Composite major adverse cardiac events (MACE) increased more in the high OPTM group of younger patients; however, MACE-free survival was similar irrespective of the extent of OPTM in older patients. Conclusions: OPTM of SERCA2 correlate with myocardial fibrosis in NICM. In younger patients, OPTM of SERCA2 correlate with elevated BNP and increased composite MACE. Keywords: SERCA2, Oxidative posttranslational modification, Myocardial fibrosis, Non-ischemic cardiomyopathy